Pengawasan Pelaksanaan Kemitraan UMKM dan Usaha Besar: Perbandingan Pengaturan di Indonesia dan Malaysia - S.H.S. Ulil Albab; Erdha Widayanto; Kevin B Sibarani (Komisi Pengawas Persaingan Usaha, 2023)
Abstract: The implementation of partnership relations between MSMEs and large businesses allows for a bargaining position gap. This scheme can actually hinder the development of MSMEs. This study aims to examine the supervision of partnerships between MSMEs and large businesses by comparing Indonesia and Malaysia as members of ASEAN which have created a Blueprint for MSME Development. Using normative juridical research methods with analytical descriptive research types and comparative studies using data sources from the literature. The results show that MyCC as the competition authority in Malaysia is not specifically responsible for supervising the implementation of partnership agreements, because competition law in Malaysia does not regulate in detail about partnership agreements so that partnerships are considered the same as other agreements in the context of business competition. Supervision of MSME partnerships in Indonesia is more effective because of the authority of the KPPU and the obligation to report partnership agreements made by MSMEs and large businesses are required to report the relevant institutions can be used to prevent potential business competition violations. Keywords: Partnership Supervision, MSMEs and Large Enterprises, Indonesia and Malaysia.